2008
DOI: 10.1007/s11269-008-9264-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential Evapotranspiration Model for Muda Irrigation Project, Malaysia

Abstract: Methods to estimate free-surface evaporation E p and potential evapotranspiration ET p using well known models, namely, Penman-Monteith model, modified Penman method, Food and Agriculture Organization Penman-Monteith (FAO-PM) method, Blaney-Criddle method, and Christiansen method, without calibrating any model calibration parameters, for monthly time series are presented. The long-term monthly averaged daily models results are calculated using recorded average historic meteorological data (1980)(1981)(1982)(19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 11 publications
(5 reference statements)
2
21
0
Order By: Relevance
“…The results of another study showed that the Hargreaves and BC equations were the best ones for Davis in California and Jagdalpur in India with arid and humid climates, respectively (George et al 2002a, b). Good performance of the BC equation may stem from its original development for humid areas where the advective effect is usually negligible and has been reported by several researchers (Irmak et al 2003a, b;Ali and Shui 2009). About inverse modelling of hydrological models, Vrugt et al (2003) presented an efficient and effective Markov Chain Monte Carlo sampler, entitled the Multiobjective Shuffled Complex Evolution Metropolis (MOSCEM) algorithm, which is capable of solving the multiobjective optimization problem for hydrological models.…”
Section: Introductionmentioning
confidence: 94%
“…The results of another study showed that the Hargreaves and BC equations were the best ones for Davis in California and Jagdalpur in India with arid and humid climates, respectively (George et al 2002a, b). Good performance of the BC equation may stem from its original development for humid areas where the advective effect is usually negligible and has been reported by several researchers (Irmak et al 2003a, b;Ali and Shui 2009). About inverse modelling of hydrological models, Vrugt et al (2003) presented an efficient and effective Markov Chain Monte Carlo sampler, entitled the Multiobjective Shuffled Complex Evolution Metropolis (MOSCEM) algorithm, which is capable of solving the multiobjective optimization problem for hydrological models.…”
Section: Introductionmentioning
confidence: 94%
“…Nowadays, this concept is practically disappeared from international literature, except in hydrology where it is considered as a robust input parameter (Douglas et al 2009) to model at catchment scale. Recent papers (Lu et al 2005;Oudin et al 2005;Weiss and Menzel 2008;Verstraeten et al 2008;Douglas et al 2009;Trajkovic and Kolakovic 2009;Hazrat Ali and Yeang Shui 2009;Donohoue et al 2010) still continue to debate and analyse differences among methods adopted in the calculation of PET.…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al (2000) has studied calculated and recorded average historic meteorological data (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997) for the Muda Agricultural Development Authority, Malaysia. This study suggests FAO-Penman Monteith method can be considered as the second best model (Ali and Lee 2008). However, this model was found to be suitable in Tanjung Karang Irrigation Scheme, Malaysia.…”
Section: Crop Evapotranspiration (Et J ) and Seepage Percolation (Sp J )mentioning
confidence: 89%